Legal Certainty of Marital Property in Mixed Marriages within the Mandalika Special Economic Zone: Marital Property in Mixed Marriages - Ayang Afira Anugerahayu; Muhammad Rifaldi Setiawan; Hera Alvina Satriawan; Nathania Permata S; Rosyia Wardani; Muh. Rifki Fitriadi (Priviet Social Sciences Journal, 2026)
Mixed marriages between Indonesian citizens and foreign nationals in international tourism areas, such as the Mandalika Special Economic Zone, give rise to various legal consequences, particularly concerning the regulation of marital property and asset ownership. The increasing cross-border socio-economic interaction within the Mandalika Special Economic Zone has contributed to the growing prevalence of mixed marriages. This condition has generated legal issues relating to the certainty of property rights, land tenure, prenuptial and postnuptial agreements, as well as legal protection for Indonesian citizens. This study aims to analyze the legal regulation of marital property in mixed marriages under Indonesian law and to examine the effectiveness of legal protection afforded to Indonesian citizens in the Mandalika Special Economic Zone. The research employs a normative-empirical method with a socio-legal approach. The normative approach examines the Marriage Law, the Indonesian Civil Code, the Basic Agrarian Law, and the Constitutional Court Decision Number 69/PUU-XIII/2015 concerning marital agreements. Meanwhile, the empirical approach explores social and administrative practices relating to asset ownership within the area. The findings demonstrate that the regulation of marital agreements and the separation of property have undergone progressive legal development. Nevertheless, its implementation remains hindered by the low level of public legal awareness, the practice of nominee agreements, limited understanding of the legal consequences of mixed marriages, and the lack of optimal harmonization between family law and agrarian law. Therefore, this study recommends strengthening legal education, optimizing the role of notaries, and reformulating regulations that are more adaptive to the dynamics of international tourism zones. These measures are expected to provide greater legal certainty and more effective legal protection for Indonesian citizens involved in mixed marriages.